The impact of disease and species differences on the intestinal CLCA4 gene expression - K. Teske; N. A. Erickson; A. Huck; M. Dzamukova; M. Fulde; T. Heinbokel; D. Horst; N. Klymiuk; E. Pastille; A. Mekes-Adamczyk; M. Löhning; A. D. Gruber; et al. (Journal of Molecular Medicine, 2025)
The human chloride channel regulator, calcium-activated (CLCA) 4 is discussed as a driver of epithelial-to-mesenchymal transition as well as a biomarker for colorectal cancer (CRC) and ulcerative colitis. In contrast to humans, the Clca4 gene is duplicated in the mouse, a common model species to study gene functions. However, the relevance of the functional murine Clca4 variants in healthy and diseased intestine is largely unknown. Here, we characterized the spatiotemporal expression patterns of the murine Clca4a and Clca4b genes in the healthy intestinal tract as well as in dextran sulfate sodium (DSS)-induced colitis and colitis-associated colon cancer (CAC) mouse model using RT-qPCR and in situ-hybridization. Similarly, we analyzed expression of the human CLCA4 in healthy, inflamed and cancerous intestinal tracts at single cell level. Murine Clca4a and - 4b but not the human CLCA4 were detected in small intestine enterocytes of the respective species. Conversely, healthy colonocytes expressed the human CLCA4 and its murine ortholog Clca4a but not the murine Clca4b . Under inflammatory conditions, de novo expression of Clca4b was observed with both murine homologs abundantly expressed in enterocytes adjacent to ulcerations. Neoplastic colonocytes expressed none or only minimal amounts of the CLCA4 homologs both in humans and mice, whereas adjacent non-neoplastic colonocytes strongly up-regulated the human or both murine homologs, respectively. Our results suggest marked species- and homolog-specific differences in the expression patterns of the three CLCA4 homologs. Moreover, all three seem to play a role in reactive, non-neoplastic colonocytes adjacent to ulcerated and neoplastic lesions. Key messages Human CLCA4 and murine Clca4a , but not Clca4b , are expressed in healthy colonocytes. Inflammation leads to a de novo expression of the murine Clca4b in colonocytes. Human and murine CLCA4 homologs are absent from neoplastic enterocytes. Human and murine CLCA4 s are highly expressed in tumor-adjacent, reactive colonocytes.